2005
DOI: 10.2188/jea.15.56
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Using Tuberculin Skin Test Erythema Measurement for Contact Investigation during a Tuberculosis Outbreak in Schoolchildren Previously Vaccinated with BCG

Abstract: BACKGROUND: Few studies have examined the validity of administering tuberculosis control measures based on tuberculin skin test (TST) erythema measurement. The present study aimed to clarify the relationship between the erythema and the induration seen following TST and to evaluate the validity of diagnosing tuberculosis infection based on the erythema following TST in school-aged contacts who had been vaccinated with bacillus Calmette-Guérin (BCG) in infancy. METHODS: A 56-month longitudinal study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These results suggest that erythema (irrespective of the induration response) could have a significant value in the interpretation of the TST results. However, in this study, no concomitant IGRA testing was performed [29]. In our study, joint assessment of induration and erythema has shown better correlation with the QFT results than when only induration was taken into account in the TST response.…”
Section: Discussionmentioning
confidence: 69%
“…These results suggest that erythema (irrespective of the induration response) could have a significant value in the interpretation of the TST results. However, in this study, no concomitant IGRA testing was performed [29]. In our study, joint assessment of induration and erythema has shown better correlation with the QFT results than when only induration was taken into account in the TST response.…”
Section: Discussionmentioning
confidence: 69%
“…Of the 36% apparently healthy individuals that had < 5 mm indurations, 29% were non-reactive. While this may indicate lower likelihood of progression to active or inactive disease (CDC 1995), anergy to PPD is a common feature among HIV infected individuals and this does not preclude to developing the disease (Toivgoogiin et al, 2005). Although retesting is sometimes recommended for negative results, this study did not follow up TST negative individuals to skin test for anergy.…”
Section: Discussionmentioning
confidence: 95%